2011
DOI: 10.1144/0016-76492011-017
|View full text |Cite
|
Sign up to set email alerts
|

Zircon U–Pb age for the Orkney lamprophyre dyke swarm, Scotland, and relations to Permo-Carboniferous magmatism in northwestern Europe

Abstract: Magmatic zircon in the syenite (bostonite) part of a composite NE–SW-trending cogenetic bostonite–camptonite dyke in Orkney, Scotland, yields a laser ablation inductively coupled plasma mass spectrometry age of 313 ± 4 Ma and ε Hf (313 Ma) values of +6 to +11. This suggests that the NE–SW-, east–west- and NW–SE-trending Scottish lamprophyre dyke swarms were emplaced during one late Carboniferous magmatic event, contrasting with published K–Ar dates ranging betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The c. 267 Ma age proposed for Group 3 structures by Dichiarante et al (2016) lies almost within error of the K-Ar age of 252 ± 10 Ma obtained for lamprophyre dykes in the Thurso area (Baxter and Mitchell 1984). Lundmark et al (2011) more recently obtained a U-Pb zircon age for a lamprophyre dyke in Orkney of 313 ± 4 Ma, which is 20-60 Ma older than the previously obtained K-Ar ages for Scottish lamprophyres. These researchers suggested that the previously obtained K-Ar ages could have been partially reset by later alteration processes and are possibly not reliable.…”
Section: Structural Relationships Associated With Ene-wsw Faults and supporting
confidence: 79%
“…The c. 267 Ma age proposed for Group 3 structures by Dichiarante et al (2016) lies almost within error of the K-Ar age of 252 ± 10 Ma obtained for lamprophyre dykes in the Thurso area (Baxter and Mitchell 1984). Lundmark et al (2011) more recently obtained a U-Pb zircon age for a lamprophyre dyke in Orkney of 313 ± 4 Ma, which is 20-60 Ma older than the previously obtained K-Ar ages for Scottish lamprophyres. These researchers suggested that the previously obtained K-Ar ages could have been partially reset by later alteration processes and are possibly not reliable.…”
Section: Structural Relationships Associated With Ene-wsw Faults and supporting
confidence: 79%
“…Near the base of the UORS are extrusive volcanic rocks (lavas), with associated volcanic vents (Halliday et al 1977). All of these rocks are cross-cut by an igneous dyke swarm dated as Permian (Lundmark et al 2011). The UORS sandstones are especially well exposed and accessible at Brough (pronounced 'broch').…”
Section: Geological Settingmentioning
confidence: 99%
“…The late Carboniferous alkaline dikes have been proposed to reflect incipient rifting signaling the start of the intense Stephanianearly Permian magmatism in north-western Europe (e.g. Lundmark et al, 2011). In northern Britain and the North Sea the Stephanianearly Permian magmatism is manifested in numerous sub-alkaline 308-290 Ma quartz-dolerite dikes and sills (Monaghan and Pringle, 2004;Monaghan and Parrish, 2006).…”
Section: Geological Settingmentioning
confidence: 99%